Effect of Addition of Composite Polyamide Micro Particles and Silicone Dioxide NanoParticle on Some Mechanical Properties of Room Temperature Vulcanized Maxillofacial Silicone Elastomer Before and after Artificial Aging - Bahaa F. Alanssari1, Bayan S. Khalaf2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The most common reason for re-making a maxillofacial prosthesis is the degradation of the mechanical properties of the silicone.Aim of this study: To assess some mechanical properties of VST-50F maxillofacial silicone reinforced with a composite of silicon dioxide nanoparticle and polyamide-6 microparticle before and after artificial aging.Material and Method: Preparing 240 samples tested for tear strength, tensile strength and elongation percentage, hardness, and roughness before and after aging. The Silicon dioxide was added in concentrations of 1% by weight and Polyamide-6 in the concentration of 0.25% and 0.5% by weight to the VST-50F RTV maxillofacial silicone. The one-way ANOVA and post hoc tests were used for inferential statistics.Results: The one-way ANOVA showed a highly significant difference between all tested groups. The effect of the addition of composite fillers showed an increase in tear strength, hardness, and surface roughness but a decrease in tensile and percentage of elongation. However, the effect of artificial aging showed increased in tear strength, Percentage of elongation, and surface roughness, but a decrease in tensile strength and hardness.Conclusion: Addition of composite of fillers into the silicone elastomer allowed enhancement of some mechanical properties. The composite of different types of filler reinforcement improves the anti-aging properties of silicone and maintain some of the mechanical properties to enhance the service life.